SEVERE HYPONATREMIA REVEALING NEUROSARCOIDOSIS - V.M. Pompilian; L.E. Stoichitoiu; S. Caraiola; P. Balanescu; R. Ionescu (Romanian Journal of Rheumatology, 2018)
Sarcoidosis is an inflammatory disease of unknown etiology, characterized by non-caseating epithelioid granulomas. Neurological involvement appears in 5-10% of cases, most frequently leading to involvement of the cranial nerves, the hypothalamus and the pituitary gland (1-3). We hereby present the case of an 82 year old woman with neurosarcoidosis who presented with severe symptomatic hyponatremia. An 82 year old woman presented to our clinic with fatigue, drowsiness, bradylalia, bradypsychia, all developed in the context of severe hyponatremia. She has been diagnosed with sarcoidosis in 2004 on the basis of histopathological examination. She has been treated with corticosteroids from 2004 until 2007; in 2007 the treatment has been stopped at the patient’s initiative. Clinical examination revealed normal cardiac and pulmonary data; there were no signs of focal neurological involvement. Lab tests showed low levels of ACTH, fT4 and an inadequate normal level of TSH, which raised the suspicion of hypopituitarism. The moderately elevated level of prolactin together with the imaging appearance (enlarged sella turcica on X-ray examination and an expansive process in the sellar and suprasellar regions on computed tomography examination) suggest that hypothalamic-pituitary insufficiency is the more accurate diagnosis. Given the background of untreated pulmonary sarcoidosis, in the absence of another sustainable etiology, we have assigned to sarcoidosis the hypothalamic-pituitary insufficiency. The outcome was good with corticosteroids in moderate dose and thyroid replacement therapy.